2005
DOI: 10.1038/ncb1335
|View full text |Cite
|
Sign up to set email alerts
|

RNA-dependent integrin α3 protein localization regulated by the Muscleblind-like protein MLP1

Abstract: We show that localized expression of the integrin α 3 protein is regulated at the level of RNA localization by the human homologue of Drosophila Muscleblind, MLP1/MBLL/MBNL2, a unique Cys 3 His zinc-finger protein. This is supported by the following observations: MLP1 knockdown abolishes localization of integrin α 3 to the adhesion complexes; MLP1 is localized in adhesion plaques that contain phospho-focal adhesion kinase; this localization is microtubule-dependent; integrin α 3 transcripts colocalize with MLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(119 citation statements)
references
References 23 publications
3
114
0
2
Order By: Relevance
“…The intensity of the MBNL1 bands in the retina appeared highest on ED15. Similar analysis with the MBNL2 antibody detected a single protein band of ca 40 kDa in both retina and muscle extracts, resembling the apparent molecular mass of human MBNL2 (Adereth et al, 2005). Based on our data, the expected size range of MBNL2 in chick is 22 kDa to 43 kDa, suggesting that the band at ϳ40 kDa is the most abundant one.…”
Section: Analysis Of Mbnl Protein Expression By Immunoblottingsupporting
confidence: 78%
See 1 more Smart Citation
“…The intensity of the MBNL1 bands in the retina appeared highest on ED15. Similar analysis with the MBNL2 antibody detected a single protein band of ca 40 kDa in both retina and muscle extracts, resembling the apparent molecular mass of human MBNL2 (Adereth et al, 2005). Based on our data, the expected size range of MBNL2 in chick is 22 kDa to 43 kDa, suggesting that the band at ϳ40 kDa is the most abundant one.…”
Section: Analysis Of Mbnl Protein Expression By Immunoblottingsupporting
confidence: 78%
“…Given that it is now well established that protein synthesis does occur in axons and synaptic terminals (Hirokawa, 2006;Martin and Zukin, 2006;Schuman et al, 2006;Wells, 2006), it is conceivable that MBNL1 may participate in the transport of mRNAs for some photoreceptor synaptic proteins toward their terminals, much as MBNL2 does in the case of the transport of integrin-␣3 mRNA toward the areas of focal adhesion complexes (Adereth et al, 2005). We are currently investigating this possibility.…”
Section: C) E-jmentioning
confidence: 98%
“…An unexpected function for MBNL2 in cytoplasmic mRNA transport has been reported, 39 but it is not yet known whether MBNL1 can also perform this function. In embryonic chick retina development, MBNL1 and MBNL2 become distributed in different regions of the photoreceptor, 52 but it is not known whether they perform similar or different functions there.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Endogenous MBNL2 has been little studied, but it does colocalize with ribonuclear foci in sections of cortical neurons 29 and heart 30 from DM1 patients and is able to regulate alternative splicing. 35 MBNL2 has also been reported to colocalize with integrin alpha3 mRNA at integrin-containing adhesion plaques, and it was suggested that MBNL2 may transport integrin alpha3 mRNA from the nucleus to the cytoplasm, 39 but the question of whether MBNL1 has a similar role was not examined. MBNL3 mRNA was present in placenta but was absent from all other tissue tested including skeletal muscle and heart.…”
Section: Functional Differences Between Mbnl1 and Mbnl2mentioning
confidence: 99%
“…Muscleblind proteins are nuclear factors that participate in the developmental regulation of alternative splicing [6,23], and they also may regulate the transport and decay of mRNA [24]. However, except for microtubuleassociated protein tau, it is not known which transcripts expressed in subsynaptic nuclei or motor neurons are subject to CUG exp -induced spliceopathy.…”
Section: Discussionmentioning
confidence: 99%